EFSA's OpenFoodTox: An open source toxicological database on chemicals in food and feed and its future developments. (January 2021) - Dorne, J.L.C.M.; Richardson, J.; Livaniou, A.; Carnesecchi, E.; Ceriani, L.; Baldin, R.; Kovarich, S.; Pavan, M.; Saouter, E.; Biganzoli, F.; Pasinato, L.; Zare Jeddi, M.; et al.
Highlights: EFSA's OpenFoodTox database contains summary hazard data for 5000 chemicals in food and feed. OpenFoodTox can be downloaded and visualised using a micro-strategy tool. Current and future development include links to in silico models and integration of New Approach Methodologies. Abstract: Since its creation in 2002, the European Food Safety Authority (EFSA) has produced risk assessments for over 5000 substances in >2000 Scientific Opinions, Statements and Conclusions through the work of its Scientific Panels, Units and Scientific Committee. OpenFoodTox is an open source toxicological database, available both for download and data visualisation which provides data for all substances evaluated by EFSA including substance characterisation, links to EFSA's outputs, applicable legislations regulations, and a summary of hazard identification and hazard characterisation data for human health, animal health and ecological assessments. The database has been structured using OECD harmonised templates for reporting chemical test summaries (OHTs) to facilitate data sharing with stakeholders with an interest in chemical risk assessment, such as sister agencies, international scientific advisory bodies, and others. This manuscript provides a description of OpenFoodTox including data model, content and tools to download and search the database. Examples of applications of OpenFoodTox in chemical risk assessment are discussed including new quantitative structure–activity relationship (QSAR) models, integration into tools (OECD QSAR Toolbox and AMBIT-2.0), assessment of environmental footprints and testing of threshold of toxicological concern (TTC) values for food related compounds. Finally, future developments for OpenFoodTox 2.0 include the integration of new properties, such as physico-chemical properties, exposure data, toxicokinetic information; and the future integration within in silico modelling platforms such as QSAR models and physiologically-based kinetic models. Such structured in vivo, in vitro and in silico hazard data provide different lines of evidence which can be assembled, weighed and integrated using harmonised Weight of Evidence approaches to support the use of New Approach Methodologies (NAMs) in chemical risk assessment and the reduction of animal testing.